COMPARISON OF SUCCESS OF EXTRACORPOREAL LITHOTRIPSY (ESWL) AND LASER URETERORENOSCOPY IN PROXIMAL URETERIC STONES - IMRAN, M; TARIQ, M; RASOOL, M; JAVAID, F; IMRAN, SMA (Biological and Clinical Sciences Research Journal, 2024)
Managing ureteral stones to achieve complete stone clearance with minimal patient morbidity involves several therapeutic approaches. The commonly used methods include extracorporeal shock wave lithotripsy (ESWL), ureteroscopy (URS), percutaneous nephrolithotripsy, laparoscopic ureterolithotomy, and open ureterolithotomy. However, definitive evidence-based options for managing large proximal ureteral stones are lacking. Objective: To compare extracorporeal shock wave lithotripsy (ESWL) and laser ureterorenoscopy (URS) success rates in treating proximal ureteric stones. Methods: This randomized controlled trial was conducted in the Department of Urology & Renal Transplantation at Bahawal Victoria Hospital, Bahawalpur, from January 1, 2020, to May 31, 2021. One hundred four patients, aged 20 to 60, with single proximal ureteric stones measuring 8-15 mm, were included. Patients with pyonephrosis, sepsis, bleeding disorders, solitary kidney, previous open ureterolithotomy, chronic renal failure, proteinuria, recurrent urinary tract infections, congenital urinary tract obstruction, bladder outflow obstruction, chronic liver disease, or a history of chronic drug usage were excluded. Patients were randomized into two groups: Group A underwent URS lithotripsy with DJ stent placement, while Group B underwent ESWL with DJ stent placement. A single surgeon performed all procedures. Pre-operative antibiotics and analgesics were administered to all patients. Stone clearance was assessed two weeks post-procedure. Statistical analysis was performed using appropriate methods, with a p-value ≤ 0.05 considered significant. Results: The mean age of patients in Group A was 37.52 ± 11.20 years, and in Group B was 36.73 ± 10.57 years. Most patients (75, 72.12%) were between 20 and 40. Out of the 104 patients, 63 (60.58%) were male, and 41 (39.42%) were female, with a male-to-female ratio of 1.7:1. Complete stone clearance was achieved in 44 (84.62%) patients in Group A (URS group) and 30 (57.69%) patients in Group B (ESWL group), with a statistically significant p-value of 0.002. The study concluded that the stone clearance rate after laser ureterorenoscopy (URS) is significantly higher than extracorporeal shock wave lithotripsy (ESWL) for proximal ureteric stones.